ELECTRON CONFINED-OPTICAL-PHONON SCATTERING RATES IN SINGLE QUANTUM-WELLS IN AN APPLIED ELECTRIC-FIELD - Weber, G; Ryan, J (1992)
We calculate the scattering rates for electron-phonon intrasubband and intersubband transitions for confined optical-phonon modes in single quantum wells when an electric field is applied parallel to the growth axis. For the description of the electron-phonon Frölich interaction we use the Huang and Zhu model, based on a lattice-dynamic approach. The scattering rates are found not to differ significantly when an electric field is applied. However, the electronconfined-phonon coupling parity presents important changes for intersubband transitions where the even phonon modes become dominant at high electric fields. For intrasubband transitions the parity changes significantly only for large quantum wells. We also present results for Fuchs-Kliewer slab model and Ridleys guided-mode model. © 1992 The American Physical Society.